An overview of the demographic situation in Ukrainian small towns - Bartosiewicz, Bartosz; Chemerys, Svitlana (Acta Universitatis Lodziensis. Folia Geographica Socio-Oeconomica, 2013)
Small cities are a popular subject in the literature on the geography of Poland. These include both important theoretical and research-based works, with the latter focused mainly on socioeconomic issues. The situation is different, however, in Ukraine, where conducting research on socioeconomics is especially difficult. The basic problem faced by researchers there is obtaining statistical data; although these difficulties may not be so serious when studying a specific region or the country as a whole, they have led to a lack of analyses of local areas, and especially of small cities. The purpose of this article is to present the diversity in the demographic potential of Ukrainian small cities; it does not provide a comprehensive analysis on the subject, but rather, offers an overview of the current state of affairs, and as such, is intended as an introduction to more extensive research. The research here will be thus focused on a comparative analysis of Poland and Ukraine.